Adaptive control of position compensation for cable-conduit mechanisms used in flexible surgical robots - Thanh Nho, Do (2014)
Natural Orifice Transluminal Endoscopic Surgery (NOTES) is a method that allows for performing complex operations via natural orifices without skin incisions. Its main tool is a flexible endoscope. Cable-Conduit Mechanisms (CCMs) are often used in NOTES because of its simplicity, safety in design, and easy transmission. Backlash hysteresis nonlinearities between the cable and the conduit pose difficulties in the motion control of the NOTES system. It is challenging to achieve the precise position of robotic arms when the slave manipulator inside the humans body. This paper presents new approaches to model and control for pairs of CCMs. It is known that the change of cable-conduit configuration will affect the backlash hysteresis nonlinearities. To deal with such change, a new nonlinear and adaptive control scheme will be introduced. The backlash hysteresis parameters are online estimated under the assumption of availability of output feedback and unknown bound of nonlinear parameters. To validate the proposed approach, a prototype of single-DOF-Master-Slave system, which consists of a master console, a telesurgical workstation, and a slave manipulator, is also presented. The proposed compensation scheme is experimentally validated using the designed system. The results show that the proposed control scheme efficiently improves the tracking performances of the system regardless of the change of endoscope configuration.